INOVASI SUMBER BELAJAR BERBASIS PROYEK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA PENGAJARAN TITRASI ASAM BASA - Pratiwi, Hilda; Sudraja, Ajat; Silaban, Ramlan (PROSIDING SEMINAR NASIONAL KIMIA; Vol 1 No 1 (2022): Prosiding SNK 2022, 2023)
Students' motivation in learning activities carried out in the laboratory really needs to be improved in order to improve Higher Order Thinking Skills in Teaching Acid-Base Titrations. This study aims to see the innovation of project-based learning resources in improving student learning outcomes in acid-base titration learning. This research is a development research with the ADDIE development model (Analysis, Design, Development, Implement, Evaluation. The subjects of this study were students of class PSPK D 2019 with purposive sampling technique. Research data were collected through innovative observation sheets of project implementation. The questionnaire refers to the eligibility criteria BSNP, and interviews.To find out the laboratory-assisted project- based learning innovation on students' learning motivation was analyzed using an independent sample t-test with the help of SPSS 25.   Keyword: Innovative, Higher Order Thinking ability, and Project-Based Learning .